Circular RNAs as Prognostic Biomarkers in Renal Cell Carcinoma: A Systematic Review and Meta-Analysis - Liao, Dan; Lin, Qiu; Xiao, Huan; Zhang, Fenglian; Han, Qin (Frontiers in Genetics, 2022)
Background: Recently, several studies have shown circRNAs play critical role in renal cell carcinoma (RCC) oncogenesis and development. However, whether the level of expression of circRNAs in RCC is correlated with the prognosis still be not clear. Hence, we conducted the meta-analysis to explore the association between the circRNAs expression level and prognosis of RCC patients. Methods: We systematically searched OVID, EMBASE, PubMed, Web of science from Jan, 1950 to June, 2021 for literature published in English. According to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we conducted a meta-analysis of 21 selected studies to confirm the association between the circRNAs expression level and prognosis of RCC. Results: This meta-analysis includes twenty articles and containing 1559 RCC patients. The result showed that oncogenic circRNAs overexpression (OS: HR=2.04, 95%CI: 1.63-2.56, P=0.20; PFS: HR=2.82, 95%CI: 0.82-9.72, P=0.03) and tumor-suppressor circRNAs lower expression (OS: HR:1.92, 95%CI: 1.61-2.30, P<0.05; PFS: HR:2.40, 95%CI: 1.76-3.28, P=0.36) was closely related with poor survival outcomes. Conclusion: The meta-analysis verifies that circRNAs can be potential prognostic biomarkers of RCC.